Circularly polarizing plate and image display device using the same

By adopting a specific layer structure and material combination in the circular polarization sheet, including a protective layer with a high glass transition temperature and an appropriate liquid crystal layer, the phase difference change and reflective tone problems of thin circular polarization sheet in a high temperature environment is solved, and a more stable and high-quality display effect is achieved.

JP7648407B2Active Publication Date: 2025-03-21NITTO DENKO CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021034318
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-04
Publication Date
2025-03-21
Estimated Expiration
2041-03-04

AI Technical Summary

Technical Problem

The existing thin circular polarized sheets are prone to phase difference changes in high temperature environments, and the reflective tone can be regarded as red, affecting the display effect.

Method used

A circular polarized sheet structure consisting of a polarized sheet, a first liquid crystal alignment curing layer, a second liquid crystal alignment curing layer and a protective layer is adopted, wherein the humidity permeability of the protective layer is controlled to be 920 g/m²·24hr or less, the flat phase difference of the first liquid crystal layer is between 100 nm and 180 nm, and the total thickness of the polarized sheet is controlled to be 100 μm or less by using a combination of a protective layer and a liquid crystal layer with a high glass transition temperature.

Benefits of technology

It effectively suppresses the phase difference changes of the circular polarization sheet in high-temperature environments, and avoids the phenomenon that the reflected tone is regarded as red, thereby improving the display quality and stability of the display device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007648407000011
    Figure 0007648407000011
  • Figure 0007648407000001
    Figure 0007648407000001
  • Figure 0007648407000002
    Figure 0007648407000002
Patent Text Reader

Abstract

To provide a thin circularly polarizing plate that suppresses a phase difference change under a high-temperature environment and also suppresses a phenomenon that reflected hue is visually recognized as red.SOLUTION: A circularly polarizing plate of the present invention includes a polarizing plate, a first liquid crystal alignment fixed layer, a second liquid crystal alignment fixed layer, and a protective layer in this order from a viewing side, and the moisture permeability of the protective layer is equal to or smaller than 920(g / m2 24 hr).SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a circular polarizing plate and an image display device using the same. [Background technology]

[0002] As flat panel displays become more widespread, displays equipped with organic electroluminescence (EL) panels have been proposed. Organic EL panels have a highly reflective metal layer, which can easily cause problems such as reflection of external light and reflection of the background. It is known that these problems can be prevented by providing a circular polarizer with a λ / 4 retardation film on the viewing side.

[0003] In recent years, as displays have become thinner, there has been a demand for thinner circular polarizing plates. However, such thin circular polarizing plates have problems such as changes in phase difference of the retardation film and reddish reflection hue when exposed to a high-temperature environment for a long period of time. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 3325560 Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention has been made to solve the above-mentioned problems of the conventional art, and its main object is to provide a thin circular polarizing plate in which the change in phase difference in a high-temperature environment is suppressed and the phenomenon in which the reflected hue is perceived as red is suppressed. [Means for solving the problem]

[0006] The circularly polarizing plate of the present invention comprises a polarizing plate, a first liquid crystal alignment solidified layer, a second liquid crystal alignment solidified layer, and a protective layer in this order from the viewing side, and the moisture permeability of the protective layer is 920 (g / m 2 24hr or less. In one embodiment, the in-plane retardation Re(550) of the first liquid crystal alignment cured layer is 100 nm to 180 nm, and satisfies the relationship of Re(450) < Re(550) < Re(650). In one embodiment, the second liquid crystal alignment cured layer exhibits a refractive index characteristic of nz > nx = ny. In one embodiment, the protective layer contains an epoxy resin or an acrylic resin, and the protective layer is a cured product or a thermoset of a coating film of an organic solvent solution of the resin. In one embodiment, the glass transition temperature of the protective layer is 85°C or higher, and the weight average molecular weight Mw of the resin is 25,000 or higher. In one embodiment, the circular polarizing plate of the present invention includes at least one additional protective layer between the polarizing plate and the first liquid crystal alignment cured layer. In one embodiment, the thickness of the circular polarizing plate of the present invention is 100 μm or less. In another aspect of the present invention, an image display device is provided. This image display device includes the above circular polarizing plate.

Advantages of the Invention

[0007] According to an embodiment of the present invention, a polarizing plate, a first liquid crystal alignment cured layer, a second liquid crystal alignment cured layer, and a protective layer are provided in this order from the viewing side, and the moisture permeability of the protective layer is 920 (g / m 2 ·24 hr) or less, thereby suppressing a change in retardation in a high-temperature environment and obtaining a thin circular polarizing plate in which the phenomenon that the reflected hue is visually recognized as red is suppressed.

Brief Description of the Drawings

[0008] [Figure 1] It is a schematic cross-sectional view of a circular polarizing plate according to one embodiment of the present invention.

Modes for Carrying Out the Invention

[0009] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.

[0010] (Definition of terms and symbols) The definitions of terms and symbols used in this specification are as follows. (1) Refractive index (nx, ny, nz) "nx" is the refractive index in the direction in which the in-plane refractive index is maximum (i.e., the slow axis direction), "ny" is the refractive index in the direction perpendicular to the slow axis in the plane (i.e., the fast axis direction), and "nz" is the refractive index in the thickness direction. (2) In-plane phase difference (Re) "Re(λ)" is the in-plane retardation measured with light of wavelength λ nm at 23° C. For example, "Re(550)" is the in-plane retardation measured with light of wavelength 550 nm at 23° C. Re(λ) is calculated by the formula: Re(λ)=(nx-ny)×d, where d(nm) is the thickness of the layer (film). (3) Retardation in the thickness direction (Rth) "Rth(λ)" is the retardation in the thickness direction measured with light of wavelength λ nm at 23° C. For example, "Rth(550)" is the retardation in the thickness direction measured with light of wavelength 550 nm at 23° C. Rth(λ) is calculated by the formula: Rth(λ)=(nx-nz)×d, where d(nm) is the thickness of the layer (film). (4) Nz coefficient The Nz coefficient is calculated by Nz=Rth / Re. (5)Angle When angles are referred to herein, the angles include both clockwise and counterclockwise angles relative to a reference direction, so for example, "45°" means ±45°.

[0011] A. Overall structure of the circular polarizer FIG. 1 is a schematic cross-sectional view of a circular polarizer according to one embodiment of the present invention. The circular polarizer 100 of the illustrated example has a polarizer 10, a first liquid crystal alignment solidified layer 20, a second liquid crystal alignment solidified layer 30, and a protective layer 40, in this order from the viewing side. The polarizer 10 typically includes a polarizer 11 and a polarizer protective film 12 arranged on the viewing side of the polarizer 11. Depending on the purpose, another polarizer protective film (not shown) may be provided on the side opposite to the viewing side of the polarizer 11. The first liquid crystal alignment solidified layer 20 is typically a retardation layer having a circular polarization function or an elliptical polarization function.

[0012] In the embodiment of the present invention, the moisture permeability of the protective layer 40 is 920 (g / m 2 By setting the moisture permeability of the protective layer in this range, a thin circular polarizing plate can be realized in which the change in retardation in a high-temperature environment is suppressed and the phenomenon in which the reflected hue is visually perceived as red is suppressed.

[0013] In one embodiment of the present invention, another protective layer may be provided between the polarizing plate and the first liquid crystal alignment solidified layer. The other protective layer may be provided in a single layer or two layers between the polarizing plate and the first liquid crystal alignment solidified layer.

[0014] The circularly polarizing plate may further include other retardation layers. The optical properties (e.g., refractive index properties, in-plane retardation, Nz coefficient, photoelastic coefficient), thickness, arrangement position, etc. of the other retardation layers may be appropriately set according to the purpose.

[0015] For practical purposes, an adhesive layer 50 may be provided as the outermost layer on the surface of the protective layer 40 opposite to the second liquid crystal alignment solidified layer 30. By providing the adhesive layer, the circular polarizer can be attached to an image display device (effectively, an image display panel). Furthermore, it is preferable that a release film is temporarily attached to the surface of the adhesive layer until the circular polarizer is used. By temporarily attaching the release film, the adhesive layer is protected and the circular polarizer can be formed into a roll.

[0016] The thickness of the circular polarizing plate is preferably 100 μm or less, more preferably 80 μm or less, even more preferably 70 μm or less, and particularly preferably 60 μm or less. The lower limit of the total thickness may be, for example, 40 μm. The thickness of the circular polarizing plate refers to the total thickness from the polarizing plate to the adhesive layer. According to the embodiment of the present invention, a very thin circular polarizing plate can be realized.

[0017] The circularly polarizing plate may be in the form of a sheet or a long sheet. In this specification, the term "long sheet" means a long and narrow shape having a sufficiently long length relative to its width, and includes, for example, a long and narrow shape having a length 10 times or more, preferably 20 times or more, relative to its width. The long circularly polarizing plate can be wound into a roll.

[0018] The components of the circularly polarizing plate will be described in more detail below. Note that the pressure-sensitive adhesive layer may have a structure known in the art, and therefore the detailed structure of the pressure-sensitive adhesive layer will not be described here.

[0019] B. Polarizing plate The polarizing plate includes a polarizer and a polarizer protective film disposed on at least one surface of the polarizer.

[0020] B-1.Polarizer Any appropriate polarizer can be used as the polarizer. For example, the resin film forming the polarizer may be a single-layer resin film or a laminate of two or more layers.

[0021] Specific examples of polarizers made of a single-layer resin film include hydrophilic polymer films such as polyvinyl alcohol (PVA) films, partially formalized PVA films, and partially saponified ethylene-vinyl acetate copolymer films that have been dyed with iodine or a dichroic substance such as a dichroic dye and stretched, and polyene-based oriented films such as dehydrated PVA films and dehydrochlorinated polyvinyl chloride films. A polarizer obtained by dyeing a PVA film with iodine and uniaxially stretching it is preferably used because of its excellent optical properties.

[0022] The dyeing with iodine is carried out, for example, by immersing the PVA-based film in an aqueous iodine solution. The stretching ratio of the uniaxial stretching is preferably 3 to 7 times. The stretching may be carried out after the dyeing treatment, or may be carried out while dyeing. Alternatively, the film may be stretched and then dyed. If necessary, the PVA-based film may be subjected to a swelling treatment, a crosslinking treatment, a washing treatment, a drying treatment, or the like. For example, by immersing the PVA-based film in water and washing it with water before dyeing, it is possible to wash off dirt and antiblocking agents on the surface of the PVA-based film, and also to swell the PVA-based film and prevent uneven dyeing.

[0023] Specific examples of polarizers obtained using laminates include a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate, or a polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer coated on the resin substrate. A polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer coated on the resin substrate can be produced by, for example, applying a PVA-based resin solution to the resin substrate and drying the resin substrate to form a PVA-based resin layer on the resin substrate to obtain a laminate of the resin substrate and the PVA-based resin layer; stretching and dyeing the laminate to make the PVA-based resin layer a polarizer. In this embodiment, stretching typically includes immersing the laminate in an aqueous solution of boric acid to stretch it. Furthermore, stretching may further include, as necessary, stretching the laminate in air at a high temperature (for example, 95°C or higher) before stretching in the aqueous solution of boric acid. The obtained laminate of resin substrate / polarizer may be used as it is (i.e., the resin substrate may be used as a polarizer protective film), or the resin substrate may be peeled off from the laminate of resin substrate / polarizer, and any suitable polarizer protective film according to the purpose may be laminated on the peeled surface. Details of the method for producing such a polarizer are described in, for example, JP-A-2012-73580 (Patent No. 5414738) and JP-A-6470455. The entire disclosure of these publications is incorporated herein by reference.

[0024] The thickness of the polarizer is preferably 25 μm or less, more preferably 1 μm to 22 μm, further preferably 1 μm to 12 μm, and particularly preferably 3 μm to 12 μm. When the thickness of the polarizer is within this range, curling during heating can be well suppressed, and good appearance durability during heating can be obtained.

[0025] The polarizer preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The single transmittance of the polarizer is 43.0% to 46.0%, as described above, and preferably 44.5% to 46.0%. The degree of polarization of the polarizer is preferably 97.0% or more, more preferably 99.0% or more, and even more preferably 99.9% or more.

[0026] B-2. Polarizer protection film The polarizer protective film is formed of any suitable film. Specific examples of the material that is the main component of the film include cellulose-based resins such as triacetyl cellulose (TAC), and transparent resins such as polyester, polyvinyl alcohol, polycarbonate, polyamide, polyimide, polyethersulfone, polysulfone, polystyrene, polynorbornene, polyolefin, (meth)acrylic, and acetate. In addition, thermosetting resins or ultraviolet-curing resins such as (meth)acrylic, urethane, (meth)acrylic urethane, epoxy, and silicone are also included. In addition, glassy polymers such as siloxane polymers are also included. In addition, the polymer films described in JP-A-2001-343529 (WO01 / 37007) can also be used. The material for this film may be, for example, a resin composition containing a thermoplastic resin having a substituted or unsubstituted imide group in the side chain, and a thermoplastic resin having a substituted or unsubstituted phenyl group and a nitrile group in the side chain, such as a resin composition containing an alternating copolymer of isobutene and N-methylmaleimide, and an acrylonitrile-styrene copolymer. The polymer film may be, for example, an extrusion molded product of the above resin composition.

[0027] The circular polarizing plate is typically arranged on the viewing side of an image display device, as described later, and the polarizer protective film 12 is typically arranged on the viewing side. Therefore, the polarizer protective film 12 may be subjected to surface treatment such as hard coat treatment, anti-reflection treatment, anti-sticking treatment, and anti-glare treatment, as necessary. Furthermore, the polarizer protective film may be subjected to treatment for improving visibility when viewed through polarized sunglasses (typically, imparting an (elliptical) polarizing function or imparting an ultra-high phase difference) as necessary. By performing such treatment, excellent visibility can be achieved even when the display screen is viewed through polarized lenses such as polarized sunglasses. Therefore, the circular polarizing plate can be suitably applied to image display devices that can be used outdoors.

[0028] In one embodiment, the other polarizer protective film is preferably optically isotropic. In this specification, "optically isotropic" means that the in-plane retardation Re(550) is 0 nm to 10 nm, and the retardation Rth(550) in the thickness direction is -10 nm to +10 nm. Preferred materials constituting the other polarizer protective film include cyclic olefin-based (e.g., polynorbornene-based), cellulose-based resins (e.g., TAC), and acrylic-based resins.

[0029] The thickness of the polarizer protective film is preferably 10 μm to 50 μm, and more preferably 10 μm to 30 μm. When the polarizer protective film is surface-treated, the thickness of the outer polarizer protective film 12 includes the thickness of the surface treatment layer.

[0030] C. First liquid crystal alignment solidification layer The first liquid crystal alignment cured layer 20 can significantly increase the difference between nx and ny compared to non-liquid crystal materials by using a liquid crystal compound. Therefore, the thickness of the first liquid crystal alignment cured layer for obtaining a desired in-plane retardation can be significantly reduced. As a result, further thinning of the circular polarizing plate can be achieved. In this specification, the "liquid crystal alignment cured layer" refers to a layer in which a liquid crystal compound is aligned in a predetermined direction within the layer and the alignment state is fixed. Note that the "alignment cured layer" is a concept that includes an alignment cured layer obtained by curing a liquid crystal monomer as described later. In this embodiment, typically, rod-shaped liquid crystal compounds are aligned in the direction of the slow axis of the first liquid crystal alignment cured layer (homogeneous alignment).

[0031] Typically, the first liquid crystal alignment cured layer exhibits a refractive index characteristic of nx > ny = nz. The first liquid crystal alignment cured layer is typically provided to impart an antireflection characteristic to the polarizing plate and can function as a λ / 4 plate. In this case, the in-plane retardation Re(550) of the first liquid crystal alignment cured layer is preferably 100 nm to 180 nm, more preferably 110 nm to 170 nm, and even more preferably 130 nm to 160 nm. Here, "ny = nz" includes not only the case where ny and nz are exactly equal but also the case where they are substantially equal. Therefore, within a range that does not impair the effects of the present invention, ny > nz or ny < nz may occur.

[0032] The Nz coefficient of the first liquid crystal alignment cured layer is preferably 0.9 to 1.5, more preferably 0.9 to 1.3. By satisfying such a relationship, when the obtained circular polarizing plate is used in an image display device, a very excellent reflected hue can be achieved.

[0033] The first liquid crystal alignment cured layer may exhibit an inverse dispersion wavelength characteristic in which the retardation value increases with the wavelength of the measurement light, a positive wavelength dispersion characteristic in which the retardation value decreases with the wavelength of the measurement light, or a flat wavelength dispersion characteristic in which the retardation value hardly changes with the wavelength of the measurement light. In one embodiment, the first liquid crystal alignment cured layer preferably exhibits an inverse dispersion wavelength characteristic. That is, the first liquid crystal alignment cured layer preferably satisfies the relationship of Re(450) < Re(550) < Re(650). In this case, Re(450) / Re(550) of the first liquid crystal alignment cured layer is preferably 0.8 or more and less than 1, more preferably 0.8 or more and 0.95 or less. With such a configuration, very excellent antireflection characteristics can be realized.

[0034] The angle θ formed between the slow axis of the first liquid crystal alignment cured layer and the absorption axis of the polarizer 11 is preferably 40° to 50°, more preferably 42° to 48°, and even more preferably about 45°. If the angle θ is within such a range, by using the first liquid crystal alignment cured layer as a λ / 4 plate as described above, a circularly polarized plate having very excellent circular polarization characteristics (as a result, very excellent antireflection characteristics) can be obtained.

[0035] The thickness of the first liquid crystal alignment cured layer is preferably 0.5 μm to 7 μm, more preferably 1 μm to 5 μm. By using a liquid crystal compound, an in-plane retardation equivalent to that of a resin film can be realized with a thickness much thinner than that of the resin film.

[0036] Examples of the liquid crystal compound include a liquid crystal compound (nematic liquid crystal) in which the liquid crystal phase is a nematic phase. As such a liquid crystal compound, for example, a liquid crystal polymer or a liquid crystal monomer can be used. The mechanism for expressing the liquid crystallinity of the liquid crystal compound may be either lyotropic or thermotropic. The liquid crystal polymer and the liquid crystal monomer may be used alone or in combination.

[0037] When the liquid crystal compound is a liquid crystal monomer, the liquid crystal monomer is preferably a polymerizable monomer and a crosslinkable monomer. This is because the alignment state of the liquid crystal monomer can be fixed by polymerizing or crosslinking (i.e., curing) the liquid crystal monomer. After the liquid crystal monomer is aligned, for example, the liquid crystal monomers can be polymerized or crosslinked with each other, thereby fixing the alignment state. Here, a polymer is formed by polymerization, and a three-dimensional network structure is formed by crosslinking, but these are non-liquid crystal. Therefore, the formed first liquid crystal alignment solidified layer does not undergo transition to a liquid crystal phase, a glass phase, or a crystal phase due to temperature changes specific to liquid crystal compounds, for example. As a result, the first liquid crystal alignment solidified layer becomes a liquid crystal alignment solidified layer that is not affected by temperature changes and has extremely excellent stability.

[0038] The temperature range in which the liquid crystal monomer exhibits liquid crystallinity varies depending on the type of the liquid crystal monomer. Specifically, the temperature range is preferably 40°C to 120°C, more preferably 50°C to 100°C, and most preferably 60°C to 90°C.

[0039] Any suitable liquid crystal monomer can be used as the liquid crystal monomer. For example, the polymerizable mesogen compounds described in JP-A-2002-533742 (WO00 / 37585), EP358208 (US5211877), EP66137 (US4388453), WO93 / 22397, EP0261712, DE19504224, DE4408171, and GB2280445 can be used. Specific examples of such polymerizable mesogen compounds include BASF's product name LC242, Merck's product name E7, and Wacker-Chem's product name LC-Sillicon-CC3767. For example, nematic liquid crystal monomers are preferred as the liquid crystal monomer.

[0040] The liquid crystal alignment solidified layer can be formed by performing an alignment treatment on the surface of a predetermined substrate, applying a coating liquid containing a liquid crystal compound to the surface to align the liquid crystal compound in a direction corresponding to the alignment treatment, and fixing the alignment state. In one embodiment, the substrate is any appropriate resin film, and the liquid crystal alignment solidified layer formed on the substrate can be transferred to the surface of an adjacent layer (e.g., a protective layer).

[0041] As the above-mentioned alignment treatment, any suitable alignment treatment can be adopted. Specifically, mechanical alignment treatment, physical alignment treatment, and chemical alignment treatment can be mentioned. Specific examples of mechanical alignment treatment include rubbing treatment and stretching treatment. Specific examples of physical alignment treatment include magnetic field alignment treatment and electric field alignment treatment. Specific examples of chemical alignment treatment include oblique deposition method and photoalignment treatment. As the treatment conditions of various alignment treatments, any suitable conditions can be adopted according to the purpose.

[0042] The alignment of the liquid crystal compound is performed by treating the liquid crystal compound at a temperature at which the liquid crystal compound exhibits a liquid crystal phase according to the type of liquid crystal compound. By performing such temperature treatment, the liquid crystal compound takes on a liquid crystal state and is aligned according to the alignment treatment direction of the substrate surface.

[0043] In one embodiment, the alignment state is fixed by cooling the liquid crystal compound aligned as described above. When the liquid crystal compound is a polymerizable monomer or a crosslinkable monomer, the alignment state is fixed by subjecting the liquid crystal compound aligned as described above to a polymerization treatment or a crosslinking treatment.

[0044] Specific examples of the liquid crystal compound and details of the method for forming the alignment solidified layer are described in JP-A-2006-163343, the disclosure of which is incorporated herein by reference.

[0045] D. Second liquid crystal alignment solidification layer The second liquid crystal alignment solidified layer may be a so-called positive C plate, which preferably exhibits a refractive index characteristic of nz>nx=ny. By using a positive C plate as the second liquid crystal alignment solidified layer, it is possible to effectively prevent reflection in an oblique direction, and the anti-reflection function can be made to have a wide viewing angle. In this case, the retardation Rth(550) in the thickness direction of the second liquid crystal alignment solidified layer is preferably -50 nm to -300 nm, more preferably -70 nm to -250 nm, further preferably -90 nm to -200 nm, and particularly preferably -100 nm to -180 nm. Here, "nx=ny" includes not only the case where nx and ny are strictly equal, but also the case where nx and ny are substantially equal. That is, the in-plane retardation Re(550) of the second liquid crystal alignment solidified layer may be less than 10 nm.

[0046] The second liquid crystal alignment solidified layer having a refractive index characteristic of nz>nx=ny may be formed of any appropriate material. The second liquid crystal alignment solidified layer is preferably made of a film containing a liquid crystal material fixed in homeotropic alignment. The liquid crystal material (liquid crystal compound) that can be homeotropically aligned may be a liquid crystal monomer or a liquid crystal polymer. Specific examples of the liquid crystal compound and the method of forming the liquid crystal alignment solidified layer include the liquid crystal compound and the method of forming the liquid crystal alignment solidified layer described in

[0020] to

[0028] of JP-A-2002-333642 (Patent No. 4174192). In this case, the thickness of the second liquid crystal alignment solidified layer is preferably 0.5 μm to 10 μm, more preferably 0.5 μm to 8 μm, and even more preferably 0.5 μm to 5 μm.

[0047] E. Protective layer As described above, the protective layer is disposed between the second liquid crystal alignment solidified layer and the adhesive layer. Furthermore, the moisture permeability of the protective layer is 920 g / m 2 - 24hr or less, preferably 900g / m 2 - 24hr or less, more preferably 880g / m 2 The lower limit of the moisture permeability of the protective layer is, for example, 700 g / m 2By disposing the protective layer between the second liquid crystal alignment solidified layer and the pressure-sensitive adhesive layer and further having a moisture permeability in this range, a thin circularly polarizing plate can be obtained in which the phase difference change in a high-temperature environment is suppressed and the phenomenon in which the reflected hue is visually perceived as red is suppressed.

[0048] The protective layer is a solidified or thermoset product of a coating film of an organic solvent solution of a resin. With this configuration, the thickness can be made very thin (for example, 10 μm or less). The thickness of the protective layer is preferably 0.01 μm to 5 μm, more preferably 0.02 μm to 3 μm, even more preferably 0.03 μm to 1 μm, and particularly preferably 0.04 μm to 0.6 μm. Furthermore, with this configuration, the protective layer can be formed directly (i.e., without an adhesive layer or a pressure-sensitive adhesive layer) on an adjacent layer (for example, a liquid crystal alignment solidified layer). According to the embodiment of the present invention, as described above, the polarizer, the liquid crystal alignment solidified layer, and the protective layer are very thin, and an adhesive layer or a pressure-sensitive adhesive layer for laminating the protective layer can be omitted, so that the total thickness of the circularly polarizing plate can be made very thin. Furthermore, such a protective layer has the advantage of being excellent in humidification durability because it has low moisture absorption and moisture permeability compared to a solidified coating film of a water-based solution such as an aqueous solution or an aqueous dispersion. As a result, a circular polarizing plate having excellent durability and capable of maintaining optical properties even under high temperature and high humidity conditions can be realized. In addition, such a protective layer can suppress the adverse effects of ultraviolet irradiation on the polarizing plate (polarizer) compared to, for example, a cured product of an ultraviolet curable resin. The protective layer is preferably a solidified product of a coating film of an organic solvent solution of the resin. The solidified product shrinks less during film formation compared to a cured product, and does not contain residual monomers, etc., so deterioration of the film itself is suppressed, and adverse effects on the polarizing plate (polarizer) caused by residual monomers, etc. can be suppressed.

[0049] Furthermore, the glass transition temperature (Tg) of the resin constituting the protective layer is 85° C. or higher, and the weight average molecular weight Mw is 25,000 or higher. If the Tg and Mw of the resin are within such ranges, the protective layer can be significantly suppressed from migrating to the image display cell of iodine in the polarizer despite being very thin, due to a synergistic effect with the effect of forming the protective layer from a solidified or thermoset product of a coating film of an organic solvent solution of the resin. The Tg of the resin is more preferably 90° C. or higher, even more preferably 100° C. or higher, particularly preferably 110° C. or higher, and most preferably 120° C. or higher. The upper limit of Tg can be, for example, 200° C. The Mw of the resin is more preferably 30,000 or higher, even more preferably 35,000 or higher, and particularly preferably 40,000 or higher. The upper limit of Mw can be, for example, 150,000.

[0050] Furthermore, the protective layer adjacent to the liquid crystal alignment solidified layer may further contain an isocyanate compound in addition to the above resin. Examples of the isocyanate compound include tolylene diisocyanate, diphenylmethane diisocyanate, xylylene diisocyanate, and derivatives thereof (e.g., modified products, adducts). The isocyanate compounds may be used alone or in combination. The content ratio of the resin and the isocyanate compound (resin / isocyanate compound) is 95 / 5 to 10 / 90 as described above. The content ratio (resin / isocyanate compound) may be, for example, 95 / 5 to 50 / 50, or, for example, 90 / 10 to 60 / 40, or, for example, 85 / 15 to 70 / 30, or, for example, 85 / 15 to 75 / 25. The content ratio (resin / isocyanate compound) may also be, for example, 40 / 60 to 5 / 95, for example, 30 / 70 to 5 / 95, or for example, 20 / 80 to 10 / 90. With such a configuration, peeling between the protective layer and the liquid crystal alignment solidified layer can be significantly suppressed.

[0051] As the resin constituting the protective layer, any suitable thermoplastic resin or thermosetting resin can be used as long as it can form a solidified or thermoset product of the coating film of the organic solvent solution and has the above-mentioned Tg and Mw. A thermoplastic resin is preferable. Examples of the thermoplastic resin include an epoxy resin and an acrylic resin. An epoxy resin and an acrylic resin may be used in combination. Representative examples of the epoxy resin and the acrylic resin that can be used in the protective layer are described below.

[0052] <Epoxy resin> As the epoxy resin, an epoxy resin having an aromatic ring is preferably used. By using an epoxy resin having an aromatic ring as the epoxy resin, when the protective layer is disposed adjacent to the polarizer, the adhesion to the polarizer can be improved. Furthermore, when the adhesive layer is disposed adjacent to the protective layer, the anchoring force of the adhesive layer can be improved. Examples of the epoxy resin having an aromatic ring include bisphenol type epoxy resins such as bisphenol A type epoxy resin, bisphenol F type epoxy resin, and bisphenol S type epoxy resin; novolac type epoxy resins such as phenol novolac epoxy resin, cresol novolac epoxy resin, and hydroxybenzaldehyde phenol novolac epoxy resin; polyfunctional epoxy resins such as glycidyl ether of tetrahydroxyphenylmethane, glycidyl ether of tetrahydroxybenzophenone, and epoxidized polyvinylphenol, naphthol type epoxy resin, naphthalene type epoxy resin, and biphenyl type epoxy resin. Preferably, bisphenol A type epoxy resin, biphenyl type epoxy resin, and bisphenol F type epoxy resin are used. Only one type of epoxy resin may be used, or two or more types may be used in combination.

[0053] <Acrylic resin> The acrylic resin typically contains a repeating unit derived from a (meth)acrylic acid ester monomer having a linear or branched structure as a main component. In this specification, (meth)acrylic refers to acrylic and / or methacrylic. The acrylic resin may contain a repeating unit derived from any appropriate copolymerization monomer depending on the purpose. Examples of the copolymerization monomer (copolymerization monomer) include a carboxyl group-containing monomer, a hydroxyl group-containing monomer, an amide group-containing monomer, an aromatic ring-containing (meth)acrylate, and a heterocycle-containing vinyl monomer. By appropriately setting the type, number, combination, and copolymerization ratio of the monomer unit, an acrylic resin having the above-mentioned predetermined Tg and Mw can be obtained.

[0054] <Boron-containing acrylic resin> In one embodiment, the acrylic resin includes a copolymer (hereinafter, sometimes referred to as a boron-containing acrylic resin) obtained by polymerizing a monomer mixture containing more than 50 parts by weight of a (meth)acrylic monomer and more than 0 part by weight and less than 50 parts by weight of a monomer represented by formula (1) (hereinafter, sometimes referred to as a copolymerization monomer): [ka] (In the formula, X represents a functional group containing at least one reactive group selected from the group consisting of a vinyl group, a (meth)acrylic group, a styryl group, a (meth)acrylamide group, a vinyl ether group, an epoxy group, an oxetane group, a hydroxyl group, an amino group, an aldehyde group, and a carboxyl group; R 1 and R 2 each independently represents a hydrogen atom, an optionally substituted aliphatic hydrocarbon group, an optionally substituted aryl group, or an optionally substituted heterocyclic group; R 1 and R 2 may be linked to each other to form a ring).

[0055] The boron-containing acrylic resin typically has a repeating unit represented by the following formula. By polymerizing a monomer mixture containing a copolymerization monomer represented by formula (1) and a (meth)acrylic monomer, the boron-containing acrylic resin has a boron-containing substituent (e.g., a repeating unit k in the following formula) in the side chain. This can improve adhesion to a polarizer when the protective layer is disposed adjacent to the polarizer. The boron-containing substituent may be contained continuously (i.e., in a block shape) or randomly in the boron-containing acrylic resin. [ka] (In the formula, R 6 represents any functional group, and j and k represent integers of 1 or more).

[0056] <(Meth)acrylic monomer> Any appropriate (meth)acrylic monomer can be used as the (meth)acrylic monomer, for example, a (meth)acrylic acid ester monomer having a linear or branched structure, or a (meth)acrylic acid ester monomer having a cyclic structure.

[0057] Examples of (meth)acrylic acid ester monomers having a linear or branched structure include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, methyl 2-ethylhexyl (meth)acrylate, and 2-hydroxyethyl (meth)acrylate. Methyl (meth)acrylate is preferably used. The (meth)acrylic acid ester monomers may be used alone or in combination of two or more.

[0058] Examples of the (meth)acrylic acid ester monomer having a cyclic structure include cyclohexyl (meth)acrylate, benzyl (meth)acrylate, isobornyl (meth)acrylate, 1-adamantyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, dicyclopentanyl (meth)acrylate, biphenyl (meth)acrylate, o-biphenyloxyethyl (meth)acrylate, o-biphenyloxyethoxyethyl (meth)acrylate, m-biphenyloxyethyl acrylate, p-biphenyloxyethyl (meth)acrylate, o-biphenyloxyethyl (meth)acrylate, Examples of the monomers include biphenyl group-containing monomers such as oxy-2-hydroxypropyl (meth)acrylate, p-biphenyloxy-2-hydroxypropyl (meth)acrylate, m-biphenyloxy-2-hydroxypropyl (meth)acrylate, N-(meth)acryloyloxyethyl-o-biphenyl=carbamate, N-(meth)acryloyloxyethyl-p-biphenyl=carbamate, N-(meth)acryloyloxyethyl-m-biphenyl=carbamate, o-phenylphenol glycidyl ether acrylate, terphenyl (meth)acrylate, o-terphenyloxyethyl (meth)acrylate, etc. Preferably, 1-adamantyl (meth)acrylate and dicyclopentanyl (meth)acrylate are used. By using these monomers, a polymer with a high glass transition temperature can be obtained. These monomers may be used alone or in combination of two or more.

[0059] Also, instead of the (meth)acrylic acid ester monomer, a silsesquioxane compound having a (meth)acryloyl group may be used. By using a silsesquioxane compound, an acrylic polymer having a high glass transition temperature is obtained. Silsesquioxane compounds having various skeletal structures, for example, cage structures, ladder structures, random structures, and the like, are known. The silsesquioxane compound may have only one of these structures, or may have two or more of them. The silsesquioxane compound may be used alone, or may be used in combination of two or more.

[0060] As the silsesquioxane compound containing a (meth)acryloyl group, for example, the MAC grade and AC grade of the SQ series of Toagosei Co., Ltd. can be used. The MAC grade is a silsesquioxane compound containing a methacryloyl group, and specific examples thereof include MAC-SQ TM-100, MAC-SQ SI-20, and MAC-SQ HDM. The AC grade is a silsesquioxane compound containing an acryloyl group, and specific examples thereof include AC-SQ TA-100 and AC-SQ SI-20.

[0061] The (meth)acrylic monomer is used in an amount of more than 50 parts by weight based on 100 parts by weight of the monomer mixture.

[0062] <Comonomer> As the copolymerization monomer, a monomer represented by the above formula (1) is used. By using such a copolymerization monomer, a boron-containing substituent is introduced into the side chain of the obtained polymer. The copolymerization monomer may be used alone or in combination of two or more kinds.

[0063] Examples of the aliphatic hydrocarbon group in the above formula (1) include a linear or branched alkyl group having 1 to 20 carbon atoms which may have a substituent, a cyclic alkyl group having 3 to 20 carbon atoms which may have a substituent, and an alkenyl group having 2 to 20 carbon atoms which may have a substituent. Examples of the aryl group include a phenyl group having 6 to 20 carbon atoms which may have a substituent, and a naphthyl group having 10 to 20 carbon atoms which may have a substituent. Examples of the heterocyclic group include a 5-membered or 6-membered ring group containing at least one heteroatom which may have a substituent. 1 and R 2 may be linked together to form a ring. 1 and R 2 is preferably a hydrogen atom or a linear or branched alkyl group having 1 to 3 carbon atoms, and more preferably a hydrogen atom.

[0064] The reactive group contained in the functional group represented by X is at least one selected from the group consisting of a vinyl group, a (meth)acrylic group, a styryl group, a (meth)acrylamide group, a vinyl ether group, an epoxy group, an oxetane group, a hydroxyl group, an amino group, an aldehyde group, and a carboxyl group. Preferably, the reactive group is a (meth)acrylic group and / or a (meth)acrylamide group. By having such a reactive group, the adhesion to the polarizer can be further improved when the protective layer is disposed adjacent to the polarizer.

[0065] In one embodiment, the functional group represented by X is preferably a functional group represented by ZY-, where Z represents a functional group containing at least one reactive group selected from the group consisting of a vinyl group, a (meth)acrylic group, a styryl group, a (meth)acrylamide group, a vinyl ether group, an epoxy group, an oxetane group, a hydroxyl group, an amino group, an aldehyde group, and a carboxyl group, and Y represents a phenylene group or an alkylene group.

[0066] Specifically, the following compounds can be used as the copolymerization monomer. [ka] [ka]

[0067] The copolymerization monomer is used in an amount of more than 0 part by weight and less than 50 parts by weight, based on 100 parts by weight of the monomer mixture, preferably 0.01 part by weight or more and less than 50 parts by weight, more preferably 0.05 to 20 parts by weight, still more preferably 0.1 to 10 parts by weight, and particularly preferably 0.5 to 5 parts by weight.

[0068] <Acrylic resin containing lactone rings, etc.> In another embodiment, the acrylic resin has a repeating unit containing a ring structure selected from a lactone ring unit, a glutaric anhydride unit, a glutarimide unit, a maleic anhydride unit, and a maleimide (N-substituted maleimide) unit. The repeating unit of the acrylic resin may contain only one type of repeating unit containing a ring structure, or may contain two or more types of repeating units containing a ring structure.

[0069] The lactone ring unit is preferably represented by the following general formula (2):

[0070] [ka] In the general formula (2), R 2 , R 3 and R 4 each independently represents a hydrogen atom or an organic residue having 1 to 20 carbon atoms. The organic residue may contain an oxygen atom. The acrylic resin may contain only a single lactone ring unit, and R 2 , R 3 and R 4 The acrylic resin may contain a plurality of lactone ring units having different ring structures. Acrylic resins having lactone ring units are described in, for example, JP-A-2008-181078, the disclosure of which is incorporated herein by reference.

[0071] The glutarimide unit is preferably represented by the following general formula (3):

[0072] [ka]

[0073] In the general formula (3), R 11 and R 12 each independently represents a hydrogen atom or an alkyl group having 1 to 8 carbon atoms; R 13 represents an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an aryl group having 6 to 10 carbon atoms. 11and R 12 are each independently a hydrogen atom or a methyl group, and R 13 is hydrogen, a methyl group, a butyl group, or a cyclohexyl group. More preferably, R 11 is a methyl group, and R 12 is hydrogen, and R 13 is a methyl group. The acrylic resin may contain only a single glutarimide unit, and R 11 , R 12 and R 13 The glutarimide unit may contain a plurality of glutarimide units having different groups. Acrylic resins having glutarimide units are described, for example, in JP-A-2006-309033, JP-A-2006-317560, JP-A-2006-328334, JP-A-2006-337491 (Patent No. 4695439), JP-A-2006-337492, JP-A-2006-337493 (Patent No. 4686261), and JP-A-2006-337569, the disclosures of which are incorporated herein by reference. Note that, for glutaric anhydride units, R 13 The above description regarding the glutarimide unit applies, except that the nitrogen atom substituted with is an oxygen atom.

[0074] As for the maleic anhydride unit and the maleimide (N-substituted maleimide) unit, their structures are specified by their names, and therefore specific explanations are omitted.

[0075] The content of the repeating unit containing a ring structure in the acrylic resin is preferably 1 mol % to 50 mol %, more preferably 10 mol % to 40 mol %, and further preferably 20 mol % to 30 mol %. The acrylic resin contains the repeating unit derived from the (meth)acrylic monomer as the main repeating unit.

[0076] The protective layer can be formed by applying an organic solvent solution of the resin as described above to form a coating film, and solidifying or thermally curing the coating film. Any appropriate organic solvent capable of dissolving or uniformly dispersing the acrylic resin can be used as the organic solvent. Specific examples of the organic solvent include ethyl acetate, toluene, methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK), cyclopentanone, and cyclohexanone. The resin concentration of the solution is preferably 3 to 20 parts by weight relative to 100 parts by weight of the solvent. With such a resin concentration, a uniform coating film can be formed.

[0077] The solution may be applied to any suitable substrate or to an adjacent layer (for example, a liquid crystal alignment solidified layer). When the solution is applied to a substrate, the solidified coating film (protective layer) formed on the substrate is transferred to the adjacent layer. When the solution is applied to an adjacent layer, the coating film is dried (solidified) to directly form a protective layer on the adjacent layer. Preferably, the solution is applied to the adjacent layer, and a protective layer is directly formed on the adjacent layer. With this configuration, the adhesive layer or pressure-sensitive adhesive layer required for transfer can be omitted, so that the circular polarizing plate can be made even thinner. Any suitable method can be adopted as a method for applying the solution. Specific examples include roll coating, spin coating, wire bar coating, dip coating, die coating, curtain coating, spray coating, and knife coating (comma coating, etc.).

[0078] The protective layer can be formed by solidifying or thermally curing the coating film of the solution. The heating temperature for solidification or thermal curing is preferably 100° C. or less, and more preferably 50° C. to 70° C. If the heating temperature is within this range, adverse effects on the polarizer can be prevented. The heating time can vary depending on the heating temperature. The heating time can be, for example, 1 minute to 10 minutes.

[0079] The protective layer (essentially, the organic solvent solution of the resin) may contain any suitable additive depending on the purpose. Specific examples of additives include ultraviolet absorbers; leveling agents; antioxidants such as hindered phenols, phosphorus, and sulfur; stabilizers such as light stabilizers, weather stabilizers, and heat stabilizers; reinforcing materials such as glass fibers and carbon fibers; near-infrared absorbers; flame retardants such as tris(dibromopropyl)phosphate, triallyl phosphate, and antimony oxide; antistatic agents such as anionic, cationic, and nonionic surfactants; colorants such as inorganic pigments, organic pigments, and dyes; organic or inorganic fillers; resin modifiers; organic or inorganic fillers; plasticizers; lubricants; antistatic agents; flame retardants; and the like. The type, number, combination, and amount of additives can be appropriately set depending on the purpose.

[0080] F. Image display device The circular polarizer described in the above items A to E can be applied to an image display device. Therefore, the embodiment of the present invention includes an image display device using such a circular polarizer. Representative examples of image display devices include liquid crystal display devices and electroluminescence (EL) display devices (e.g., organic EL display devices, inorganic EL display devices). The image display device according to the embodiment of the present invention includes the circular polarizer described in the above items A to E on the viewing side. The circular polarizer is laminated so that the liquid crystal alignment solidified layer is on the image display cell (e.g., liquid crystal cell, organic EL cell, inorganic EL cell) side (so that the polarizer is on the viewing side). In one embodiment, the image display device has a curved shape (substantially a curved display screen) and / or is bendable or foldable. EXAMPLES

[0081] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The methods for measuring each property are as follows. In the examples and comparative examples, "parts" and "%" are by weight unless otherwise specified.

[0082] (1) Thickness The thickness of 10 μm or less was measured using an interference film thickness meter (manufactured by Otsuka Electronics, product name "MCPD-3000"), and the thickness of more than 10 μm was measured using a digital micrometer (manufactured by Anritsu, product name "KC-351C"). (2) Glass transition temperature (Tg) The glass transition temperature of the resin was measured using a differential scanning calorimeter DSC6220 manufactured by SII Nano Technology. Approximately 10 mg of the resin sample was placed in an aluminum pan manufactured by the same company and sealed, and the temperature was raised from 30°C to 200°C at a heating rate of 20°C / min under a nitrogen gas flow of 50 mL / min. After holding the temperature for 3 minutes, the sample was cooled to 30°C at a rate of 20°C / min. The sample was held at 30°C for 3 minutes and then heated again to 200°C at a rate of 20°C / min. From the DSC data obtained in the second heating, the extrapolated glass transition onset temperature, which is the temperature at the intersection of a straight line extending the low-temperature baseline to the high-temperature side and a tangent drawn at the point where the gradient of the curve of the step-like change in the glass transition is maximum, was calculated and used as the glass transition temperature (Tg). (3) Moisture permeability The protective layers obtained in the examples and comparative examples were applied to triacetyl cellulose (TAC) films, and the moisture permeability (g / m) was measured under test conditions of 40°C and 90% RH using Technolox's "DELTAPERM". 2 -24hr) was measured. (4) Phase difference value A sample of 50 mm x 50 mm was cut out from the retardation film obtained in the examples and comparative examples to prepare a measurement sample. The in-plane retardation of the prepared measurement sample was measured using a retardation measuring device (product name "KOBRA21-ADH") manufactured by Oji Scientific Instruments Co., Ltd. The measurement wavelength of the in-plane retardation was 590 nm, and the measurement temperature was 23°C. (5) Change in phase difference due to heating The circularly polarizing plates obtained in the examples and comparative examples were attached to glass via an adhesive layer to prepare samples, and the retardation was measured in the same manner as in the retardation measurement described above. After the measurement, the samples were placed in an environment of 85°C for 120 hours, and then taken out and the retardation was measured again to determine the change rate (%) of Re(590). Good: The absolute value of the phase difference change rate (%) is less than 0.9%. Poor: The absolute value of the phase difference change rate (%) is 0.9% or more. (6) Red discoloration The circularly polarizing plates obtained in the Examples and Comparative Examples were attached to a glass plate via an adhesive and subjected to a heating test at 100° C. for 120 hours, and the appearances before and after the heating test were visually observed. Good: No redness was observed Poor: Redness was observed

[0083] [Production Example 1: Preparation of boron-containing acrylic resin] 97.0 parts by weight of methyl methacrylate (MMA, Fujifilm Wako Pure Chemical Industries, Ltd., product name: methyl methacrylate monomer), 3.0 parts by weight of a monomer of general formula (1e), and 0.2 parts by weight of a polymerization initiator (Fujifilm Wako Pure Chemical Industries, Ltd., product name: 2,2'-azobis(isobutyronitrile)) were dissolved in 200 parts by weight of toluene. Next, a polymerization reaction was carried out for 5.5 hours while heating to 70°C under a nitrogen atmosphere, to obtain Copolymer 1 (solid content concentration: 33% by weight). Copolymer 1 had a Tg of 110°C and a weight average molecular weight of 80,000.

[0084] [Production Example 2: Preparation of Polarizing Plate A] 1. Preparation of Polarizer A The thermoplastic resin substrate was a long amorphous isophthalic copolymerized polyethylene terephthalate film (thickness: 100 μm) having a water absorption rate of 0.75% and a Tg of about 75° C. One side of the resin substrate was subjected to a corona treatment. A PVA aqueous solution (coating solution) was prepared by adding 13 parts by weight of potassium iodide to 100 parts by weight of a PVA-based resin made by mixing polyvinyl alcohol (polymerization degree 4200, saponification degree 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., product name "GOHSEFFIMER Z410") in a ratio of 9:1, and dissolving the mixture in water. The above PVA aqueous solution was applied to the corona-treated surface of a resin substrate and dried at 60° C. to form a PVA-based resin layer with a thickness of 13 μm, thereby producing a laminate. The obtained laminate was uniaxially stretched at its free end to 2.4 times its original size in the machine direction (longitudinal direction) between rolls with different peripheral speeds in an oven at 130° C. (auxiliary air stretching treatment). Next, the laminate was immersed in an insolubilizing bath (a boric acid aqueous solution obtained by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilizing treatment). Next, the film was immersed in a dye bath (iodine aqueous solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 with 100 parts by weight of water) at a liquid temperature of 30°C for 60 seconds while adjusting the concentration so that the single transmittance (Ts) of the final polarizer would be 43.0% or more (dyeing process). Next, the piece was immersed in a crosslinking bath (a boric acid aqueous solution obtained by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment). Thereafter, the laminate was immersed in an aqueous boric acid solution (boric acid concentration 4.0% by weight, potassium iodide concentration 5% by weight) at a liquid temperature of 70°C and uniaxially stretched in the longitudinal direction (longitudinal direction) between rolls with different peripheral speeds so that the total stretch ratio was 5.5 times (underwater stretching treatment). Thereafter, the laminate was immersed in a cleaning bath (an aqueous solution obtained by mixing 4 parts by weight of potassium iodide with 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment). Thereafter, while drying in an oven maintained at 90°C, the laminate was brought into contact with a SUS heated roll whose surface temperature was maintained at 75°C for approximately 2 seconds (drying shrinkage treatment). The shrinkage rate of the laminate in the width direction due to the drying shrinkage treatment was 5.2%. In this manner, a polarizer A having a thickness of 5 μm was formed on the resin substrate.

[0085] 2. Preparation of Polarizing Plate A An HC-TAC film was attached as a polarizer protective film to the surface of the polarizer A obtained above (the surface opposite to the resin substrate) via an ultraviolet-curable adhesive. Specifically, the curable adhesive was applied so that the total thickness was 1.0 μm, and the films were attached using a rolling machine. Then, the adhesive was cured by irradiating UV rays from the polarizer protective film side. The HC-TAC film was a film in which a hard coat (HC) layer (thickness 7 μm) was formed on a triacetyl cellulose (TAC) film (thickness 25 μm), and the TAC film was attached to the polarizer side. Next, the resin substrate was peeled off to obtain a polarizing plate A having a configuration of HC layer / TAC film / adhesive layer / polarizer A.

[0086] [Production Example 3: Preparation of Polarizing Plate B] A polarizing plate B was obtained in the same manner as in Production Example 1, except that an HC-COP film was used as the polarizer protective film. The HC-COP film is a film in which a hard coat (HC) layer (thickness 2 μm) is formed on a cycloolefin (COP) film (manufactured by Zeon Corporation, product name "ZF12", thickness 25 μm).

[0087] [Production Example 4: Preparation of Polarizing Plate C] A polarizing plate C was obtained using the polarizer A obtained in Production Example 1 in the same manner as in Production Example 1, except that an acrylic film (thickness: 20 μm) was used as the polarizer protective film.

[0088] [Production Example 5: Production of Polarizing Plate D] A long roll of a 30 μm-thick polyvinyl alcohol film (manufactured by Kuraray, product name "PE3000") was uniaxially stretched in the long direction to 5.9 times its original length using a roll stretching machine while simultaneously undergoing swelling, dyeing, crosslinking, and washing treatments, and finally drying treatment to obtain a 12 μm-thick polarizer D. A similar HC-TAC film to that polarizer D in Production Example 1 was bonded as a polarizer protective film to that polarizer D via a PVA-based adhesive. Next, the resin substrate was peeled off, and a triacetyl cellulose (TAC) film (thickness 25 μm) was bonded to the released surface via a PVA-based adhesive to obtain a polarizing plate D.

[0089] [Production Example 6: Preparation of Polarizing Plate E] A polarizing plate E was obtained in the same manner as in Production Example 1, except that an HC-TAC film was used as a polarizer protective film and was attached using a PVA-based adhesive.

[0090] [Production Example 7: Preparation of the first liquid crystal alignment solidified layer and the second liquid crystal alignment solidified layer] 1. Preparation of the first liquid crystal alignment layer 55 parts of the compound represented by formula (I), 25 parts of the compound represented by formula (II), and 20 parts of the compound represented by formula (III) were added to 400 parts of cyclopentanone (CPN), and then the mixture was heated to 60°C and stirred to dissolve. After dissolution was confirmed, the mixture was returned to room temperature, and 3 parts of Irgacure 907 (manufactured by BASF Japan Ltd.), 0.2 parts of Megafac F-554 (manufactured by DIC Corporation), and 0.1 parts of p-methoxyphenol (MEHQ) were added and further stirred to obtain a solution. The solution was transparent and uniform. The obtained solution was filtered through a 0.20 μm membrane filter to obtain a polymerizable composition. On the other hand, the polyimide solution for the alignment film was applied to a glass substrate having a thickness of 0.7 mm by spin coating, dried at 100°C for 10 minutes, and then baked at 200°C for 60 minutes to obtain a coating film. The obtained coating film was subjected to rubbing treatment to form an alignment film. The rubbing treatment was performed using a commercially available rubbing device. The polymerizable composition obtained above was applied to a substrate (substantially an alignment film) by spin coating, and dried at 100° C. for 2 minutes. After the obtained coating film was cooled to room temperature, it was irradiated with 30 mW / cm 2 of a high-pressure mercury lamp. 2 The first liquid crystal alignment layer was irradiated with ultraviolet light at an intensity of 100 nm for 30 seconds to obtain a first liquid crystal alignment layer. The first liquid crystal alignment layer had an in-plane retardation Re(550) of 130 nm. The liquid crystal alignment layer had a Re(450) / Re(550) of 0.851, and showed reverse dispersion wavelength characteristics.

[0091] [ka] [ka]

[0092] 2. Preparation of the second liquid crystal alignment layer A liquid crystal coating liquid was prepared by dissolving 20 parts by weight of a side-chain liquid crystal polymer represented by the following chemical formula (I) (the numbers 65 and 35 in the formula indicate the mol% of the monomer unit, and are conveniently represented as a block polymer: weight average molecular weight 5000), 80 parts by weight of a polymerizable liquid crystal exhibiting a nematic liquid crystal phase (manufactured by BASF: trade name Paliocolor LC242), and 5 parts by weight of a photopolymerization initiator (manufactured by Ciba Specialty Chemicals: trade name Irgacure 907) in 200 parts by weight of cyclopentanone. Then, the coating liquid was applied to a substrate film (norbornene-based resin film: manufactured by Nippon Zeon Co., Ltd., trade name "Zeonex") using a bar coater, and then the liquid crystal was aligned by heating and drying at 80°C for 4 minutes. The liquid crystal layer was irradiated with ultraviolet light to harden the liquid crystal layer, thereby forming a second liquid crystal alignment solidified layer (thickness: 0.58 μm) on the substrate. This layer had Re(550) of 0 nm and Rth(550) of -80 nm, and exhibited refractive index characteristics of nz>nx=ny.

[0093] [ka]

[0094] [Example 1] On the first liquid crystal alignment solidified layer obtained in Production Example 7, the boron-containing acrylic resin prepared in Production Example 1 was applied so that the thickness after drying was 0.5 μm, to form another protective layer. Next, the polarizing plate E obtained in Production Example 6 was laminated on the surface of the other protective layer via an acrylic adhesive (thickness 5 μm). Next, the second liquid crystal alignment solidified layer obtained in Production Example 7 was transferred to the opposite side of the first liquid crystal alignment solidified layer from the polarizer. At this time, they were laminated so that the angle between the absorption axis of the polarizer and the slow axis of the first liquid crystal alignment solidified layer was +45°. Note that each transfer (lamination) was performed via the ultraviolet-curing adhesive (thickness 1.0 μm) used in Production Example 2. In this way, a laminate having a configuration of HC layer / TAC film / adhesive layer / polarizer / acrylic adhesive layer / another protective layer / first liquid crystal alignment solidified layer / adhesive layer / second liquid crystal alignment solidified layer was produced.

[0095] 15 parts (solid content equivalent) of the copolymer 1 (boron-containing acrylic resin) obtained in Production Example 1 and 85 parts (solid content equivalent) of a thermoplastic epoxy resin (manufactured by Mitsubishi Chemical Corporation, trade name "jER (registered trademark) YX6954BH30") were blended. The Tg of the resin blend was 125°C and the weight average molecular weight was 46000. This mixture was dissolved in 80 parts of a mixed solvent of ethyl acetate / cyclopentanone (70 / 30) to obtain a resin solution (20%). This resin solution was applied to the second liquid crystal alignment solidified layer surface of the laminate obtained above using a wire bar, and the applied film was dried at 60°C for 5 minutes to form a protective layer (thickness 0.5 μm) constituted as a solidified product of the applied film of the organic solvent solution of the resin. Next, an adhesive layer (thickness 15 μm) was provided on the surface of the protective layer to obtain a circular polarizing plate having a structure of HC layer / TAC film / adhesive layer / polarizer / acrylic adhesive layer / another protective layer / first liquid crystal alignment solidified layer / adhesive layer / second liquid crystal alignment solidified layer / protective layer / adhesive layer. The moisture permeability of the protective layer was 869.8 (g / m 2 The total thickness of the resulting circularly polarizing plate was 65 μm. The resulting circularly polarizing plate was subjected to the above evaluations (4) to (6). The results are shown in Table 1.

[0096] [Example 2] To 95 parts of a blend of 15 parts (solid content equivalent) of Copolymer 1 (boron-containing acrylic resin) obtained in Production Example 1 and 85 parts (solid content equivalent) of a thermoplastic epoxy resin (manufactured by Mitsubishi Chemical Corporation, product name "jER (registered trademark) YX6954BH30"), 5 parts of an isocyanate compound (manufactured by Tosoh Corporation, "Coronate L": trimethylolpropane adduct of tolylene diisocyanate). The Tg of the resin blend was 23°C and the weight average molecular weight was 50,000. Using this mixture, a circularly polarizing plate was obtained in the same manner as in Example 1. The moisture permeability of the protective layer was 901.7 (g / m 2 The total thickness of the obtained circularly polarizing plate was 65 μm. The obtained circularly polarizing plate was subjected to the above-mentioned evaluations (4) to (6). The results are shown in Table 1.

[0097] [Comparative Example 1] A circularly polarizing plate was obtained in the same manner as in Example 1, except that no protective layer was provided between the second liquid crystal alignment solidified layer and the adhesive layer. The total thickness of the obtained circularly polarizing plate was 64 μm. The obtained circularly polarizing plate was subjected to the above evaluations (4) to (6). The results are shown in Table 1.

[0098] [Comparative Example 2] A circularly polarizing plate was obtained in the same manner as in Example 1, except that a trimethylolpropane / tolylene diisocyanate trimer adduct (manufactured by Nippon Polyurethane Industry Co., Ltd., product name "Coronate L") was used as the protective layer between the second liquid crystal alignment solidified layer and the adhesive layer. The moisture permeability of the protective layer was 944.6 (g / m 2 The total thickness of the obtained circularly polarizing plate was 66 μm. The obtained circularly polarizing plate was subjected to the above-mentioned evaluations (4) to (6). The results are shown in Table 1.

[0099] [Example 3] A circularly polarizing plate was obtained in the same manner as in Example 1, except that polarizing plate B was used as the polarizing plate. The total thickness of the obtained circularly polarizing plate was 61 μm. The obtained circularly polarizing plate was subjected to the above evaluations (4) to (6). The results are shown in Table 1.

[0100] [Example 4] A circular polarizing plate was obtained in the same manner as in Example 2, except that polarizing plate B was used as the polarizing plate. The total thickness of the obtained circular polarizing plate was 61 μm. The obtained circular polarizing plate was subjected to the above evaluations (4) to (6). The results are shown in Table 1.

[0101] [Comparative Example 3] A circularly polarizing plate was obtained in the same manner as in Example 3, except that no protective layer was provided between the second liquid crystal alignment solidified layer and the adhesive layer. The total thickness of the obtained circularly polarizing plate was 60 μm. The obtained circularly polarizing plate was subjected to the above evaluations (4) to (6). The results are shown in Table 1.

[0102] [Example 5] A circular polarizing plate was obtained in the same manner as in Example 2, except that polarizing plate C was used as the polarizing plate. The total thickness of the obtained circular polarizing plate was 54 μm. The obtained circular polarizing plate was subjected to the above evaluations (4) to (6). The results are shown in Table 1.

[0103] [Comparative Example 4] A circularly polarizing plate was obtained in the same manner as in Example 5, except that no protective layer was provided between the second liquid crystal alignment solidified layer and the adhesive layer. The total thickness of the obtained circularly polarizing plate was 53 μm. The obtained circularly polarizing plate was subjected to the above evaluations (4) to (6). The results are shown in Table 1.

[0104] [Example 6] A circular polarizing plate was obtained in the same manner as in Example 1, except that polarizing plate D was used as the polarizing plate. The total thickness of the obtained circular polarizing plate was 96 μm. The obtained circular polarizing plate was subjected to the above evaluations (4) to (6). The results are shown in Table 1.

[0105] [Comparative Example 5] A circularly polarizing plate was obtained in the same manner as in Example 5, except that no protective layer was provided between the second liquid crystal alignment solidified layer and the adhesive layer. The total thickness of the obtained circularly polarizing plate was 95 μm. The obtained circularly polarizing plate was subjected to the above evaluations (4) to (6). The results are shown in Table 1.

[0106] [Example 7] A circular polarizing plate was obtained in the same manner as in Example 1, except that polarizing plate A was used as the polarizing plate. The total thickness of the obtained circular polarizing plate was 65 μm. The obtained circular polarizing plate was subjected to the above evaluations (4) to (6). The results are shown in Table 1.

[0107] [Comparative Example 6] A circularly polarizing plate was obtained in the same manner as in Example 7, except that no protective layer was provided between the second liquid crystal alignment solidified layer and the adhesive layer. The total thickness of the obtained circularly polarizing plate was 64 μm. The obtained circularly polarizing plate was subjected to the above evaluations (4) to (6). The results are shown in Table 1.

[0108] [Example 8] A circularly polarizing plate was obtained in the same manner as in Example 1, except that polarizing plate A was used and the copolymer obtained in Production Example 1 was not applied to the first liquid crystal alignment solidified layer. The total thickness of the obtained circularly polarizing plate was 65 μm. The obtained circularly polarizing plate was subjected to the above evaluations (4) to (6). The results are shown in Table 1.

[0109] [Comparative Example 7] A circularly polarizing plate was obtained in the same manner as in Example 8, except that no protective layer was provided between the second liquid crystal alignment solidified layer and the adhesive layer. The total thickness of the obtained circularly polarizing plate was 64 μm. The obtained circularly polarizing plate was subjected to the above evaluations (4) to (6). The results are shown in Table 1.

[0110] [Table 1]

[0111] [evaluation] As is clear from Table 1, the circular polarizers of the examples of the present invention suppress the change in retardation in a heated environment. Furthermore, it is understood that the circular polarizers of the examples of the present invention suppress the red discoloration of the circular polarizers. [Industrial Applicability]

[0112] The circular polarizing plate of the present invention is suitably used as a circular polarizing plate for liquid crystal displays, organic EL displays, and inorganic EL displays. [Explanation of symbols]

[0113] 10 Polarizing plate 11 Polarizer 12 Polarizer protection film 20 First liquid crystal alignment solidification layer 30 Second liquid crystal alignment solidification layer 40 protective layer 50 Adhesive layer 100 Circular polarizer

Claims

1. A polarizing plate, a first liquid crystal alignment solidified layer, a second liquid crystal alignment solidified layer, a protective layer, and a pressure-sensitive adhesive layer in this order (excluding the case where a base material is interposed between the second liquid crystal alignment solidified layer and the pressure-sensitive adhesive layer), The moisture permeability of the protective layer is 920 (g / m 2 - 24 hr) or less, The thickness of the protective layer is 0.01 μm or more and 5 μm or less. Circular polarizer.

2. 2. The circularly polarizing plate according to claim 1, wherein the first liquid crystal alignment solidified layer has an in-plane retardation Re(550) of 100 nm to 180 nm and satisfies the relationship Re(450)<Re(550)<Re(650).

3. 3. The circular polarizer according to claim 1, wherein the second liquid crystal alignment solidified layer exhibits a refractive index characteristic of nz>nx=ny.

4. 4. The circular polarizing plate according to claim 1, wherein the protective layer contains an epoxy resin or an acrylic resin, and is a solidified or heat-cured coating film of a solution of the epoxy resin or the acrylic resin in an organic solvent.

5. 5. The circularly polarizing plate according to claim 4, wherein the protective layer has a glass transition temperature of 85° C. or higher, and the epoxy resin or the acrylic resin has a weight average molecular weight Mw of 25,000 or higher.

6. The circular polarizer of claim 1 , further comprising at least one additional protective layer between the polarizer and the first liquid crystal alignment solidified layer.

7. The circularly polarizing plate according to claim 1 , which has a thickness of 100 μm or less.

8. An image display comprising the circular polarizer according to claim 1 .

Citation Information

Patent Citations

  • Optical film for organic el display devices, polarizing film for organic el display devices, polarizing film with adhesive layer for organic el display devices, and organic el display device

    JP2017203835A

  • Rubber-based adhesive composition, rubber-based adhesive layer, adhesive film, optical film with rubber-based adhesive layer, optical member, and image display device

    JP2018039863A

  • Optical laminate and picture display unit

    JP2018060015A

  • Polarizing plate

    JP2019120951A

  • Retardation film and optical device using the same

    JP3325560B2